Effect of green leaves used in traditional food preparations on DNA repair - Arpitha Y R (Department of Plant Biotechnology, College of Agriculture, 2009)
The thesis entitled “Effect of green leaves used in traditional food preparation on DNA repair” was conducted at the Department of Plant Biotechnology, College of Agriculture, Vellayani, Thirvananthapuram during 2007-2009 with an objective to test the effect of green leaf extracts of plants (Azima tetracantha, Cissampelos pareira, Myxopyrum serratulum, Pongamia pinnata and Thespesia populneus) used in traditional food preparations on DNA repair by employing the Comet Assay.